A Time-Dose Response Model to Assess Diuron-Induced Photosynthesis Inhibition in Freshwater Biofilms - Morin, Soizic; Chaumet, Betty; Mazzella, Nicolas (Frontiers in Environmental Science, 2018)
Contamination by herbicides is reported in most freshwater environments. These biologically active compounds may impact the non-target biota such as benthic biofilms, at the base of the trophic chain. In agricultural watersheds, herbicides occur as pulses in the system, and traditional dose-response analysis performed at a given duration of exposure (hours to days) may not predict accurately the risk of adverse impacts at shorter temporal scales (minutes to hours) corresponding to pulse exposures. To assess the time-response relationship in biofilms exposed to herbicides, we used diuron, an inhibitor of photosynthesis, to perform bioassays (time-response curves) with the aim of characterizing the initial steps of photosynthesis decrease after exposure to the herbicide (from seconds to hours), for different concentrations of exposure. Diuron-induced inhibition of photosynthesis reflects blockage of electron transfer in PSII, therefore we defined the time lag to reach the threshold of 50 % photosynthesis inhibition (t1/2) as the time for diuron to reach its target site (adsorption, distribution). We found a rapid decrease in photosynthetic efficiency: t1/2 values were dose-dependent and ranged from <30 seconds (highest concentration of exposure) to 7’20’’ (lowest concentration). While dose-response curves are influenced by the initial biomass or nature of biofilms, time-response curves yielded similar t1/2 for contrasted biofilms, making this parameter a unique response to be valuably incorporated into an ecotoxicology framework. We also assessed the variability of the response as a function of previous short-term (3 hours) exposure to diuron. The t1/2 values obtained were consistent with those obtained on non-exposed biofilms, but repeated pulses of diuron exacerbated the decrease in photosynthetic yields. This time-response approach highlighted that diuron reaches its cellular target almost instantaneously (< 1 minute), independently of biological parameters (chlorophyll a concentration, adaptation related to exposure history). Reversibility of toxic impacts a few hours after diuron removal was not fully demonstrated, suggesting that the kinetics of diuron release from cells to uncontaminated medium are much slower than binding rates. Our results confirm that repeated exposure is very likely to impair freshwater biofilms, in particular if pulses occur at high frequency.